2013
DOI: 10.5551/jat.13201
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein Cholesterol in Coronary Artery Disease: When Higher Means Later

Abstract: Aim: Although high-density lipoprotein cholesterol (HDL-C) levels are inversely associated with cardiovascular risk, patients with elevated HDL-C also develop coronary artery disease (CAD) and cardiac events. We aimed to draw the clinical profile of CAD patients with elevated HDL-C and to assess the prognostic impact of elevated HDL-C. Methods: We prospectively examined 2322 patients (age 67±10 years, 79% male) with chronic CAD, defined by >50% coronary stenosis and/or previous myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…We also provided subgroup analyses in whole population as followed: (a) smokers vs non-smokers, (b) diabetics vs non-diabetics, (c) statin-treated vs non-treated patients, and (d) controlled vs uncontrolled hypertensives in order to investigate any differences in HDL-C and PBR 5-9 levels within the above-mentioned groups as well as the relationship between HDL-C and PBR [5][6][7][8][9] in each group separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also provided subgroup analyses in whole population as followed: (a) smokers vs non-smokers, (b) diabetics vs non-diabetics, (c) statin-treated vs non-treated patients, and (d) controlled vs uncontrolled hypertensives in order to investigate any differences in HDL-C and PBR 5-9 levels within the above-mentioned groups as well as the relationship between HDL-C and PBR [5][6][7][8][9] in each group separately.…”
Section: Discussionmentioning
confidence: 99%
“…Increased perfusion boundary region (PBR) of the sublingual arterial microvessels (ranging from 5 to 9 µm) using Sideview Darkfield imaging (Microscan, Glycocheck) was measured as a non-invasive accurate index of reduced EG thickness. PBR [5][6][7][8][9] was significantly decreased in group HDL H (P = 0.04). In the whole population, HDL-C was inversely but moderately related to PBR 5-9 (r = −0.22, P = 0.01).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, they are not widely used in clinical practice due to the lack of validated methods to assess these parameters, which is also mentioned by experts in existing guidelines 1. We also should not forget other, “less sophisticated”, biochemical markers of cardiovascular risk with proved antioxidative role such as HDL‐C 9, 10, lipoprotein A, 11, C‐reactive protein 12, and other lipid parameters 13, 14, although again in accordance with the guidelines they are of limited importance 1. The interpretation of this study should also take into account relatively small population of patients with most severe coronary artery disease – with multivessel disease – where intense and wider risk profile assessment could be reasonable.…”
Section: Recommendations For Lipid Analyses For Screening For Cardiovmentioning
confidence: 99%
“…However, HDL‐C levels are influenced by many factors that also influence CVD risk . Interestingly, Sbrana et al recently concluded that also patients with elevated HDL‐C may develop CVD but later in life . In addition, a recent Mendelian randomization study provides strong evidence that genetic mechanisms raising HDL‐C do not always confer lower risk of myocardial infarction .…”
mentioning
confidence: 99%